A Comparative Evaluation for Biologic Width following Surgical Crown Lengthening Using Gingivectomy and Ostectomy Procedure - Kiran Kumar Ganji; Veena Ashok Patil; Jiji John (Hindawi Limited, 2012)
Surgical crown lengthening has been proposed as a means of facilitating restorative procedures and preventing injuries in teeth with structurally inadequate clinical crown or exposing tooth structure in the presence of deep, subgingival pathologies which may hamper the access for proper restorative measures. Histological studies utilizing animal models have shown that postoperative crestal resorption allowed reestablishment of the biologic width. However, very little has been done in humans. Aims. The purpose of the study was to evaluate the potential changes in the periodontal tissues, particularly the biologic width, following surgical crown lengthening by two surgical procedures before and after crown placement. Methods and Material. Twenty (20) patients who needed surgical crown lengthening to gain retention necessary for prosthetic treatment and/or to access caries, tooth fracture, or previous prosthetic margins entered the study. The following parameters were obtained from line angles of treated teeth (teeth requiring surgical crown lengthening) and adjacent sites: Plaque and Gingival Indices (PI) & (GI), Position of Gingival Margin from reference Stent (PGMRS), Probing depth (PD), and Biologic Width (BW). Statistical Analysis Used. Student "t" Test. Results. Initial baseline values of biologic width were 2.55 mm (Gingivectomy procedure B1 Group) and 1.95 mm (Ostectomy procedure B2 Group) and after surgical procedure the values were 1.15 mm and 1.25 mm. Conclusions. Within the limitations of the study the biologic width, at treated sites, was re-established to its original vertical dimension by 3 months. Ostectomy with apically positioned flap can be considered as a more effective procedure than Gingivectomy for Surgical Crown Lengthening.